Physical Exercise Modulates Brain Physiology Through a Network of Long- and Short-Range Cellular Interactions - Consorti, Alan; Di Marco, Irene; Sansevero, Gabriele (Frontiers in Molecular Neuroscience, 2021)
In the last decades, the effects of sedentary lifestyles have emerged as a critical aspect of modern society. Interestingly, recent evidence demonstrated that physical exercise plays an important role not only in maintaining peripheral health but also in the regulation of central nervous system function. Many studies have shown that physical exercise promotes the release of molecules, involved in neuronal survival, differentiation, plasticity and neurogenesis, from several peripheral organs. Thus, aerobic exercise has emerged as an intriguing tool that, on one hand, could serve as a therapeutic protocol for diseases of the nervous system, and on the other hand, could help to unravel potential molecular targets for pharmacological approaches. In the present review, we will summarize the cellular interactions that mediate the effects of physical exercise on brain health, starting from the factors released in myocytes during muscle contraction to the cellular pathways that regulate higher cognitive functions, in both health and disease.